Pop masculinities the politics of gender in twenty-first century popular music - Hansen, Kai Arne ca. 20./21. Jh (Oxford University Press, 2021)
In this work, Kai Arne Hansen investigates the performance and policing of masculinity in pop music as a starting point for grasping the broad complexity of gender and its politics in the early 21st century. Drawing together perspectives from critical musicology, gender studies, and adjacent scholarly fields, the book presents extended case studies of five well-known artists: Zayn, Lil Nas X, Justin Bieber, The Weeknd, and Take That. By directing particular attention to the ambiguities and contradictions that arise from these artists' representations of masculinity, Hansen argues that pop performances tend to operate in ways that simultaneously reinforce and challenge gender norms and social inequalities
Also issued in print: 2022. - Includes bibliographical references and index
Keywords: Popular music / History and criticism; Masculinity in music